Geschlecht, Bildung, Profession : Ungleichheiten im pädagogischen Berufsfeld - Burren, Susanne Dr; Larcher-Klee, Sabina Prof. Dr; Joris, Elisabeth; Makarova, Elena Prof. Dr; Ziegler, Béatrice Prof. Dr; Lindner, Jana; Wenger, Nadine; Baumgarten, Diana Dr; Kappler, Christa Dr; Hupka-Brunner, Sandra Dr; Leemann, Regula Julia Prof. Dr; Pfeifer Brändli, Andrea; et al. (Studien zu Differenz, Bildung und Kultur ;, 2021)
Gender inequalities in society as a whole are also reflected in the professional field of education. The anthology deals with ongoing and new problems in pedagogical professions from the perspective of the history of the profession, educational system and occupational sociology. This shows the interweaving of professional history and gender relations, from which insights for professional development can also be derived.